2022
DOI: 10.1038/s41420-022-01033-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IL8 as a sequential therapy strategy to overcome chemotherapy resistance in advanced gastric cancer

Abstract: Systemic chemotherapy with multiple drug regimens is the main therapy option for advanced gastric cancer (GC) patients. However, many patients develop relapse soon. Here, we evaluated the therapeutic potential of targeting interleukin-8 (IL8) to overcome resistance to chemotherapy in advanced GC. RNA sequencing revealed crucial molecular changes after chemotherapy resistance, in which the expression of IL8 was significantly activated with the increase in drug resistance. Subsequently, the clinical significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Studies have shown that CSCs function as a major driving force of drug-resistance and they are deeply involved in the pathogenesis of drug resistance ( 192 , 193 ). Targeting cytokine/receptor signals holds promise for overcoming drug resistance and restoring sensitivity to anticancer therapies ( 77 , 194 ). For example, IL-4 has been reported to protect CRC CSCs from apoptosis and the potential benefits of standard chemotherapies, radiotherapies or immunotherapies in combination with IL-4 inhibitors may enhance the therapeutic efficacy in the context of CRC ( 77 ).…”
Section: Clinical Implications For Crc Development Prevention and Tre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that CSCs function as a major driving force of drug-resistance and they are deeply involved in the pathogenesis of drug resistance ( 192 , 193 ). Targeting cytokine/receptor signals holds promise for overcoming drug resistance and restoring sensitivity to anticancer therapies ( 77 , 194 ). For example, IL-4 has been reported to protect CRC CSCs from apoptosis and the potential benefits of standard chemotherapies, radiotherapies or immunotherapies in combination with IL-4 inhibitors may enhance the therapeutic efficacy in the context of CRC ( 77 ).…”
Section: Clinical Implications For Crc Development Prevention and Tre...mentioning
confidence: 99%
“…A study by Jiang et al. ( 194 ) assessed the efficacy of targeting IL.-8 signaling to overcome drug resistance in advanced gastric cancer, and their results showed that increased expression of IL8 significantly activated drug resistance. IL8 signaling targeted by RNA interference or reparixin reversed chemotherapy resistance with limited toxicity in vivo and in vitro .…”
Section: Clinical Implications For Crc Development Prevention and Tre...mentioning
confidence: 99%
“…In vivo and in vitro experiments showed that IL8-targeted by RNA interference or reparixin reversed chemotherapy resistance with limited toxicity. Consequently, it was shown that the sequential treatment with first and second-line chemotherapy followed by reparixin inhibited the growth of GC and reduced the toxicity of the treatment and prolonged survival of mice [ 32 ] ( Table 1 ). Some limitations exist in this study, including no exploration of the biology of the IL-8 system in myeloid leukocyte populations present in immunodeficient mice, and IL-8 absence from the rodent genome [ 32 ] ( Table 1 ).…”
Section: The Role Of Interleukins In the Mechanism Of Chemoresistance...mentioning
confidence: 99%
“…Consequently, it was shown that the sequential treatment with first and second-line chemotherapy followed by reparixin inhibited the growth of GC and reduced the toxicity of the treatment and prolonged survival of mice [ 32 ] ( Table 1 ). Some limitations exist in this study, including no exploration of the biology of the IL-8 system in myeloid leukocyte populations present in immunodeficient mice, and IL-8 absence from the rodent genome [ 32 ] ( Table 1 ). The above data suggest that the assessment of IL-8 levels in GC patients may be useful as a predictive biomarker in monitoring drug resistance in these patients.…”
Section: The Role Of Interleukins In the Mechanism Of Chemoresistance...mentioning
confidence: 99%
“…However, increasing numbers of studies have shown that surgery cannot benefit patients with unresectable AGC and post-operative complication is a negative predictor of long-term survival outcomes for them (9). Systemic chemotherapy with multiple drug regimens is the main therapy choice to further prolong the survival of post-or non-operative AGC patients (10). Despite relevant progress, the impact of chemotherapy on AGC patients' survival is still unsatisfactory, especially patients with multiple distant metastases (1).…”
Section: Introductionmentioning
confidence: 99%